Development of acid‐base‐enzyme pretreatment and hydrolysis of palm oil mill effluent for bioethanol production - Deb, Nibedita; Alam, Md. Zahangir; Rashid Al-khatib, Maan Fahmi; Elgharbawy, Amal A.M. (Scrivener Publishing, 2019)
Nowadays, palm oil mill effluent (POME) is the main water stream pollutant in Malaysia. This paper reviews the development in the methods of bioethanol production from POME by acid-base-enzyme pretreatment and hydrolysis processes. The methods currently used to treat POME are inefficient in terms of either cost or environmental preservation. Several techniques of pretreatment of POME are discussed, where the structure of POME is broken down and made more accessible to the cellulase enzymes. Generally, hydrolysis process is used as a mild acid-base-enzyme for monomeric sugar production from POME. The acid-base-enzyme consists of H2SO4, NaOH and cellulase enzymes to run the hydrolysis process. In this paper, different strategies are also described for hydrolysis processes, including concentrate acid, dilute acid and enzymatic hydrolysis. In addition, the production of bioethanol by fermentation of sugars obtained from the hydrolysis process is discussed and it points out some key properties that should be targeted for cost-effective and innovative pretreatment processes.